\( V \) \[ \begin{array}{l}\text { Suppose that the functions } r \text { and } s \text { are defined for all real numbers } x \text { as follows. } \\ r(x)=x+1 \\ s(x)=3 x^{2}\end{array} \] Whte the expressions for \( (r-s)(x) \) and \( (r+s)(x) \) and exaluate \( (r-s)(-1) \). \( \begin{array}{l}(r-s)(x)=\square \\ (r+s)(x)=\square \\ (r-s)(-1)=\square\end{array} \)
Solución de tutoría real
Responder
Solución
Revisado y aprobado por el equipo de tutoría de UpStudy
Mind Expander
To find the expressions for \( (r-s)(x) \) and \( (r+s)(x) \), we can use the definitions of the functions \( r(x) \) and \( s(x) \). First, for \( (r-s)(x) \): \[ (r-s)(x) = r(x) - s(x) = (x + 1) - (3x^2) = -3x^2 + x + 1 \] Next, for \( (r+s)(x) \): \[ (r+s)(x) = r(x) + s(x) = (x + 1) + (3x^2) = 3x^2 + x + 1 \] Now, to evaluate \( (r-s)(-1) \): \[ (r-s)(-1) = -3(-1)^2 + (-1) + 1 = -3(1) - 1 + 1 = -3 - 1 + 1 = -3 \] So the completed expressions are: \[ \begin{array}{l} (r-s)(x) = -3x^2 + x + 1 \\ (r+s)(x) = 3x^2 + x + 1 \\ (r-s)(-1) = -3 \end{array} \]